Composition basics and analysis of visual language of the product - Markova, Kremena (International Journal of Engineering and Management Sciences, 2019)
The analysis of the visual language of the product demands deeper analysis of the user’s profile and built behavioral patterns. There is an existing group of factors that have relatively constant nature - gender differentiation, age differentiation, belongingness to specific group – social status, place in hierarchy, race, religion, people with special needs, etc. The analysis of the visual language of the product can be done by analyzing the basic arsenal of the composition - the means of composing form shaping: scale –related to the correct size of the products and their components; proportions –associated with organizing the form plastical and visual order of the whole and its parts; contrast - related to the shape of the product, semantical or bounded to past experience; color –bounded to both formal characteristics and plasticity, as well as to contrast and its meaningful designation; plastic of the form - linked to the proportions and scale, which determines not only the structural and formal characteristics of the products, but also the meaningful reading of the forms. The analysis of the individual composite devices is demonstrated by Ingo Maurer’s lighting fixtures.